Stress–Strain Behaviour of Modified 9Cr–1Mo Steel in Asymmetric Cyclic Stressing at Room Temperature - Mishra P.; Rajpurohit R.S.; Srinivas N.C.S.; Singh V. (My University, 2025)
Asymmetric cyclic stressing of structural components causes accumulation of plastic strain known as ratcheting. It is an important factor in design of nuclear power plants as the accumulated plastic strain causes severe reduction in life of the structural components. Operating variables such as the rate of stressing (Formula Presented), mean stress (σm) and amplitude of stress (σa) control the ratcheting fatigue behaviour. Fatigue tests were conducted with σm from 190–210 MPa, σa from 400 to 420 MPa and the (Formula Presented) from 50 to 450 MPa/s. The accumulation of plastic strain and its influence on cyclic life of the modified 9Cr–1Mo steel was studied. Increase in the σm and σa led to the increase in the accumulated plastic strain and reduction in fatigue life. On the other hand, increase in the (Formula Presented) caused increase in fatigue life because of less plastic strain accumulation. There was cyclic softening with increase in σm and σa, whereas there was cyclic hardening from rise in the (Formula Presented). © 2020, Springer Nature Singapore Pte Ltd.